Antioxidant high-temperature-resistant ceramic panel and preparation method thereof
By using a combination technology of liquid ceramic organic precursor and ceramic particles, an oxidation-resistant high-temperature ceramic panel was prepared, which solved the problem of insufficient temperature resistance of existing ceramic panels in high temperature environments and achieved good mechanical properties of the panels in an environment of 1700℃.
Patent Information
- Application Number
- CN202411752036.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-14
AI Technical Summary
When used in an environment above 1500°C, the current ceramic panels are insufficient in temperature resistance and cannot meet the requirements of the severe aerodynamic thermal environment generated by high-speed flight of the aircraft.
The liquid ceramic organic precursor is used to mix it with the catalyst, and low-melting point ceramic particles and functional ceramic particles are added, and cured by negative pressure impregnation and oxygen-depleted curing, and finally high-temperature pyrolysis is carried out under an inert environment to prepare an oxidation-resistant high-temperature ceramic panel.
It has achieved good mechanical strength of ceramic panels under an aerobic environment of 1700℃, which solves the problem of insufficient temperature resistance of existing ceramic panels and is suitable for sandwich structure thermal protection materials in the aerospace field.
Smart Images

Figure CN119613134A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an oxidation-resistant and high-temperature-resistant ceramic panel and a preparation method thereof, belongs to the field of preparation of ceramic-based composite materials, and is expected to be applied to panels of sandwich structure thermal protection materials in the aerospace field. Background Art
[0002] Thermal protection technology is a key factor in the success or failure of aircraft design. During high-speed flight, the aircraft will be subjected to severe compression and friction from the air in front, and the kinetic energy will be rapidly converted into thermal energy, causing the temperature of the air around the aircraft to rise sharply and generate strong aerodynamic heat. If there is a lack of reliable thermal protection technology, many electronic equipment of the aircraft will be exposed to high temperatures in this aerodynamic thermal environment, affecting the safe and stable flight of the aircraft. Sandwich structure thermal protection material is a thermal protection material prepared by integrating the core layer of lightweight thermal insulation material and the upper and lower layers of high temperature resistant and erosion resistant panels through stitching. It has the advantages of simple structure, high efficiency thermal insulation, and erosion resistance, and is widely used in aircraft thermal protection systems. The thermal insulation performance of sandwich structure thermal protection materials is mainly determined by the core layer of lightweight thermal insulation materials. The core layer generally uses lightweight and low thermal conductivity materials such as aerogels and foams with rich pore structures. The erosion resistance of sandwich structure thermal protection materials is determined by the panel. The panel generally uses high-density fiber-reinforced ceramic matrix composite materials. Improving the heat resistance and erosion resistance of the panel is very important for the sandwich structure thermal protection material to withstand the aerodynamic heat flow erosion generated by the high-speed flight of the aircraft.
[0003] Chinese patent application CN108032580A discloses a method for preparing a sandwich structure thermal protection material and a thermal protection material prepared by the method. The panel fabric is impregnated with an organic resin such as epoxy resin to prepare a panel with high surface strength, which can effectively block heat flow and improve the thermal insulation and anti-scouring properties of the material. However, due to the temperature resistance of the resin used in the panel, the applicable temperature of the panel prepared by the method is relatively low. Chinese patent application CN108116002A discloses a sandwich structure thermal protection material with high panel strength and a manufacturing method thereof. The panel fabric is impregnated with a water-soluble ceramic sol to prepare a high-temperature resistant panel, which can withstand 1000°C heat treatment and has a tensile strength of not less than 40MPa. Chinese patent application CN113563093A discloses a lightweight high-temperature resistant sandwich thermal protection material and a preparation method thereof. The panel fabric is impregnated with a homemade alumina sol to prepare a high-temperature resistant panel, which can withstand 1500°C heat treatment. The tensile strength of the panel before heat treatment is greater than 80MPa, and the tensile strength of the panel after heat treatment is greater than 20MPa.
[0004] At present, the preparation of high temperature resistant panels is mainly through the impregnation of high temperature resistant ceramic fiber fabrics with ceramic sol. Ceramic sol is mainly an aqueous dispersion of nano ceramic particles such as silicon dioxide and alumina. Ceramic fiber fabrics are mainly quartz cloth, mullite cloth, etc. Limited by the melting point of the panel itself, these prepared panels are difficult to use in an environment above 1500°C. As the speed of aircraft increases, aircraft will face a more severe aerodynamic thermal environment. The existing ceramic panels can no longer meet the temperature resistance requirements of aircraft interlayer thermal protection materials. It is necessary to develop panels with higher temperature resistance to meet the needs of aircraft with increasing flight speeds. Summary of the invention
[0005] In order to improve the above-mentioned sandwich structure thermal protection material high temperature resistant panel and preparation method, the present invention provides an antioxidant and high temperature resistant ceramic panel and a preparation method thereof, which realizes the preparation of antioxidant and high temperature resistant ceramic panels without the need for repeated impregnation and cracking, thereby compensating for the problem of insufficient temperature resistance of existing sandwich structure thermal protection material panels, and is expected to meet the requirements of the aerospace field for sandwich structure thermal protection material panels with higher temperature resistance.
[0006] To achieve the above object, the specific technical solution of the present invention is a method for preparing an oxidation-resistant and high-temperature resistant ceramic panel, comprising the following steps:
[0007] (1) heating and drying the cut and interlayer-stitched carbon fiber cloth in an oven to obtain a panel fabric;
[0008] (2) mixing the liquid ceramic organic precursor and the catalyst uniformly, and then adding low melting point ceramic particles and functional ceramic particles and dispersing them uniformly to obtain a ceramic organic precursor impregnation liquid;
[0009] (3) impregnating the ceramic organic precursor impregnation liquid in (2) into the panel fabric under negative pressure;
[0010] (4) curing the panel fabric impregnated in (3) in an oxygen-deficient environment to obtain a ceramic organic precursor panel;
[0011] (5) The ceramic organic precursor panel obtained in (4) is subjected to high-temperature pyrolysis in an inert environment to finally obtain an antioxidant and high-temperature resistant ceramic panel.
[0012] Furthermore, the ceramic organic precursor is one or more of liquid polycarbosilane, liquid polysiloxane, liquid polyborosilazane and the like.
[0013] Furthermore, the low-melting-point ceramic particles are glass powder, and the melting point of the glass powder ranges from 600°C to 1000°C.
[0014] Furthermore, the functional ceramic particles may be one or more ceramic particles selected from silicon hexaboride, molybdenum disilicide, zirconium diboride and the like.
[0015] Furthermore, the particle size of the functional ceramic particles ranges from 500 nm to 10 μm.
[0016] Furthermore, the pyrolysis temperature of the ceramic organic precursor panel ranges from 900°C to 1200°C.
[0017] Furthermore, the carbon fiber cloth is one of the carbon fiber cloths of models such as T300, T400, T800, etc.
[0018] The present invention also provides an oxidation-resistant and high-temperature-resistant ceramic panel prepared by the method.
[0019] In the above technical solution, the liquid ceramic organic precursor has a certain viscosity, and the ceramic particles can be well dispersed stably without the need to add additional dispersants.
[0020] The principle of the present invention is that small molecules are released when the ceramic organic precursor is cracked, which will produce holes and gaps inside the material. Therefore, when using the ceramic organic precursor to prepare fiber fabric reinforcement materials, the fiber fabric needs to be repeatedly impregnated and cracked to fill and shrink the holes and gaps. By adding low-melting-point ceramic particles and functional ceramic particles to the ceramic organic precursor, when the ceramic organic precursor is cracked in a high-temperature environment, the low-melting-point ceramic particles will form a molten viscous state and carry the functional ceramic particles to self-level and seal the holes and gaps produced by the cracking, thereby ensuring the density and integrity of the material after cracking.
[0021] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0022] 1. The raw materials of the present invention are commercial raw materials, which are easy to prepare and do not involve complicated processes.
[0023] 2. The present invention can appropriately introduce functional ceramic particles to enrich the applicable environment of the panel while ensuring the temperature resistance and integrity of the panel.
[0024] 3. The present invention can achieve the densification of the panel without the repeated impregnation and cracking required by the traditional ceramic organic precursor process.
[0025] 4. The antioxidant and high-temperature resistant ceramic panel prepared by the present invention can withstand 1700°C treatment in an aerobic environment and still maintain good mechanical strength. It has the characteristics of simple process, functional adjustment, and a wide range of applications. It can be used as a panel of thermal protection materials for sandwich structures in the aerospace field. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1This is a physical picture of the anti-oxidation ceramic panel in Example 1;
[0027] Figure 2 This is the tensile curve of the anti-oxidation ceramic panel in Example 1 after being treated with oxygen at 1700° C. for 1000 s;
[0028] Figure 3 This is the tensile curve of the anti-oxidation ceramic panel in Example 2 after being treated with oxygen at 1700°C for 1000s. DETAILED DESCRIPTION
[0029] The following is combined with Figures 1 to 3 The present invention is further described with examples:
[0030] Embodiment 1:
[0031] An anti-oxidation and high-temperature resistant ceramic panel and a preparation method thereof, comprising the following steps:
[0032] (1) Ten pieces of carbon fiber cloth with a size of 150 mm × 150 mm were cut and sewn together in the thickness direction with carbon fiber, and then placed in a 90°C oven for 2 h to obtain a panel fabric for use.
[0033] (2) Weigh 3 g of diisopropylbenzene peroxide and add it to 300 g of liquid polycarbosilane, stirring to dissolve, then add 15 g of glass powder with a melting point of 900° C. and 15 g of silicon hexaboride ceramic particles, and stir vigorously to evenly disperse the ceramic particles to obtain a polycarbosilane impregnation solution.
[0034] (3) The polycarbosilane impregnation liquid in (2) is impregnated into the panel fabric in (1) under the condition of not more than 1 kPa.
[0035] (4) The panel fabric in (3) was cured in a nitrogen-blown oven at 120° C. for 1 h, 150° C. for 1 h, 190° C. for 2 h, and 210° C. for 5 h to obtain a polycarbosilane panel.
[0036] (5) The polycarbosilane panel obtained in (4) was heated to 1000° C. at a heating rate of 1° C. / min in a nitrogen atmosphere and kept at this temperature for 2 h for high-temperature pyrolysis, thereby finally obtaining an antioxidant and high-temperature resistant ceramic panel.
[0037] The thickness of the finally prepared anti-oxidation and high-temperature resistant ceramic panel is 2 mm and the density is 2.3 g / cm 3 , after being treated at 1700℃ in an aerobic environment for 1000s, the tensile strength is not less than 20MPa.
[0038] Figure 1 This is a real picture of the anti-oxidation ceramic panel. It can be seen that the panel surface is dense and has no holes or cracks.
[0039] Figure 2 This is the tensile curve of the anti-oxidation ceramic panel after being treated with oxygen at 1700℃ for 1000s. It can be seen that the panel still has good mechanical properties after high temperature treatment.
[0040] Embodiment 2:
[0041] An anti-oxidation and high-temperature resistant ceramic panel and a preparation method thereof, comprising the following steps:
[0042] (1) Ten pieces of carbon fiber cloth with a size of 150 mm × 150 mm were cut and sewn together in the thickness direction with carbon fiber, and then placed in a 90°C oven for 2 h to obtain a panel fabric for use.
[0043] (2) Weigh 300 g of liquid polysiloxane, add 15 g of glass powder with a melting point of 1000° C. and 25 g of molybdenum disilicide ceramic particles, and stir vigorously to evenly disperse the ceramic particles to obtain a polysiloxane impregnation solution.
[0044] (3) The polysiloxane impregnation liquid in (2) is impregnated into the panel fabric in (1) under the condition of not more than 1 kPa.
[0045] (4) The panel fabric in (3) was cured in a nitrogen-blown oven at 90° C. for 4 h, 150° C. for 4 h, and 220° C. for 4 h to obtain a polysiloxane panel.
[0046] (5) The polysiloxane panel obtained in (4) was heated to 1200° C. at a heating rate of 1° C. / min in a nitrogen atmosphere and kept at this temperature for 2 h for high-temperature pyrolysis to finally obtain an antioxidant and high-temperature resistant ceramic panel.
[0047] The thickness of the finally prepared anti-oxidation and high-temperature resistant ceramic panel is 2 mm and the density is 2.5 g / cm 3 , after being treated at 1700℃ in an aerobic environment for 1000s, the tensile strength is not less than 20MPa.
[0048] Figure 3 This is the tensile curve of the anti-oxidation ceramic panel after being treated with oxygen at 1700℃ for 1000s. It can be seen that the panel still has good mechanical properties after high temperature treatment.
[0049] Embodiment 3:
[0050] An anti-oxidation and high-temperature resistant ceramic panel and a preparation method thereof, comprising the following steps:
[0051] (1) Ten pieces of carbon fiber cloth with a size of 150 mm × 150 mm were cut and sewn together in the thickness direction with carbon fiber, and then placed in a 90°C oven for 2 h to obtain a panel fabric for use.
[0052] (2) Weigh 300 g of liquid polyborosilazane, add 10 g of glass powder with a melting point of 900° C. and 25 g of zirconium diboride ceramic particles, and stir vigorously to evenly disperse the ceramic particles to obtain a polyborosilazane impregnation solution.
[0053] (3) The polyborosilazane impregnation liquid in (2) is impregnated into the panel fabric in (1) under the condition of not more than 1 kPa.
[0054] (4) The panel fabric in (3) was cured in a nitrogen-blown oven at 120° C. for 3 h, 180° C. for 4 h, and 240° C. for 4 h to obtain a polyborosilazane panel.
[0055] (5) The polyborosilazane panel obtained in (4) was heated to 1200° C. at a heating rate of 1° C. / min in a nitrogen atmosphere, and kept at this temperature for 2 h for high-temperature pyrolysis, thereby finally obtaining an antioxidant and high-temperature resistant ceramic panel.
[0056] The thickness of the finally prepared anti-oxidation and high-temperature resistant ceramic panel is 2 mm and the density is 2.1 g / cm 3 , after being treated at 1700℃ in an aerobic environment for 1000s, the tensile strength is not less than 20MPa.
[0057] The specific embodiments of the present invention disclosed above are intended to help understand the content of the present invention and implement it accordingly. It can be understood by those skilled in the art that various replacements, changes and modifications are possible without departing from the spirit and scope of the present invention. The present invention should not be limited to the contents disclosed in the embodiments of this specification, and the scope of protection of the present invention shall be subject to the scope defined in the claims.
Claims
1. A method for preparing an oxidation-resistant and high-temperature-resistant ceramic panel, characterized in that: The following steps are involved: The cut and interlayer-stitched carbon fiber cloth is heated and dried in an oven to obtain a panel fabric; The liquid ceramic organic precursor and the catalyst are mixed evenly, and then low melting point ceramic particles and functional ceramic particles are added and dispersed evenly to obtain a ceramic organic precursor impregnation liquid; Impregnating the panel fabric with a ceramic organic precursor impregnation liquid under negative pressure; The impregnated panel fabric is cured in an oxygen-deficient environment to obtain a ceramic organic precursor panel; The ceramic organic precursor panel is subjected to high-temperature pyrolysis in an inert environment to obtain an oxidation-resistant and high-temperature resistant ceramic panel.
2. The preparation method according to claim 1, characterized in that: The ceramic organic precursor is one or more of liquid polycarbosilane, liquid polysiloxane, liquid polyborosilazane and the like.
3. The preparation method according to claim 1, characterized in that: The low melting point ceramic particles are glass powder, and the melting point of the glass powder ranges from 600°C to 1000°C.
4. The preparation method according to claim 1, characterized in that: The functional ceramic particles are one or more ceramic particles such as silicon hexaboride, molybdenum disilicide, and zirconium diboride.
5. The preparation method according to claim 1, characterized in that: The particle size range of the functional ceramic particles is 500nm-10μm.
6. The preparation method according to claim 1, characterized in that: The pyrolysis temperature of the ceramic organic precursor panel ranges from 900°C to 1200°C.
7. The preparation method according to claim 1, characterized in that: The carbon fiber cloth is one of the carbon fiber cloths of models T300, T400 and T800.
8. An antioxidant and high temperature resistant ceramic panel prepared according to the method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Method for preparing sandwich structured thermal protection material and thermal protection material prepared according to method
CN108032580A
Sandwich structure thermal protection material with high panel strength and making method thereof
CN108116002A
Lightweight high-temperature-resistant interlayer thermal protection material and preparation method thereof
CN113563093A
Preparation method for low-density refractory and antioxidative carbon-ceramic composite material
CN106565262A
Lightweight high-temperature resistant thermal protection material and preparation method thereof
CN108585947A